2015
DOI: 10.1177/0883073815570151
|View full text |Cite
|
Sign up to set email alerts
|

Fears in the General Population

Abstract: This study aimed to examine the structure of fears of youth, and its associations with gender, genetic variation of the serotonin transporter (5-HTTLPR), and perceived maternal acceptance/rejection and control, in a population-representative sample. Participants were 453 adolescents and 540 young adults. Fears were assessed by a 18-item Fear Questionnaire, and perceived maternal relationships by the Mother Acceptance-Rejection/Control Questionnaire. A structured psychiatric interview was used to assess current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although aggression and impulsivity have been found to be associated with Internet addiction ( Cao, Su, Liu, & Gao, 2007 ; Ko, Yen, Liu, Huang, & Yen, 2009 ; Koo & Kwon, 2014 ; Yen et al., 2007 ), our findings contradict a report stating that females use mobile phones to socialize ( Bianchi & Phillips, 2005 ). Considering the higher level of fear among females ( Tulviste, Kiive, Akkermann, & Harro, 2015 ), smartphone use may allow them to express their anger or hostility in a way that they regard as being socially more acceptable. If this hypothesis is valid, a longitudinal study should examine whether such use would ultimately represent an adaptive or maladaptive coping strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Although aggression and impulsivity have been found to be associated with Internet addiction ( Cao, Su, Liu, & Gao, 2007 ; Ko, Yen, Liu, Huang, & Yen, 2009 ; Koo & Kwon, 2014 ; Yen et al., 2007 ), our findings contradict a report stating that females use mobile phones to socialize ( Bianchi & Phillips, 2005 ). Considering the higher level of fear among females ( Tulviste, Kiive, Akkermann, & Harro, 2015 ), smartphone use may allow them to express their anger or hostility in a way that they regard as being socially more acceptable. If this hypothesis is valid, a longitudinal study should examine whether such use would ultimately represent an adaptive or maladaptive coping strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SERT promoter gene polymorphism may potentially play a role in identifying, subgrouping, and selecting treatment strategies. In addition, in a population-representative study consisting of 540 young adults and 453 adolescents, scientists revealed that the 5-HTTLPR genotype plays a key role in the association between phobia (fears) and perceived relations and a history of psychiatric disorder observed in participants who had S/S-genotype of 5-HTTLPR [56]. It is supposed that SAD entails an overactive presynaptic serotonergic system affecting the rate of serotonin biosynthesis and activity of tryptophan hydroxylase that, in turn, appears functionally influenced by the TPH2 G-703T polymorphism in the emotionally relevant regions of the brain [57,58].…”
Section: Serotonin-related Mechanisms In the Etiology And Treatment O...mentioning
confidence: 99%